Current treatment of older patients with recurrent gynecologic cancer. Issue 5 (October 2019) - Yoshida, Yoshio
Abstract : Purpose of review: Gynecologic cancer patients of elderly has been increasing rapidly. Useful information on older patients, especially, with recurrent gynecological cancer is extremely limited. Recent findings: A unified concept for assessing treatment risk was proposed when providing cancer treatment to older patients. Fit: patients capable of withstanding the same standard treatment as healthy younger patients; Vulnerable: patients incapable of withstanding the same standard treatment as healthy younger patients, but capable of undergoing some sort of treatment; and Frail: patients incapable of withstanding the same standard treatment as healthy younger patients, and also unsuitable to undergo any kind of active treatment. It is important to identify vulnerability by using geriatric assessment as a patient background factor, to intervene if treatment is required, and to modify the intensity of treatment in an attempt to extend overall survival, decrease adverse events, improve health-related quality of life, and reduce medical costs. Summary: It is important to carry out a pretreatment functional assessment of older cancer patients using the geriatric assessment, and to choose the method of treatment for older patients in light of its results with recurrent gynecological cancer in addition to chronological age.